2013
DOI: 10.1111/sltb.12054
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Suicide Ideators from Attempters: Violence—A Research Note

Abstract: Which factors distinguish suicide attempters from suicide ideators is a relatively neglected question in suicidology. Data from the 2001 Youth Risk Behavior Survey, encompassing 1,439 youth suicide ideators and 1,097 attempters, was used to explore which factors best differentiate suicide attempters from ideators, with a focus on violence involvement. Measures of violence include the contexts of fights, dating, and weapons carrying. Controls were incorporated for psychiatric disorders, risky sexual behavior, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 21 publications
7
39
0
2
Order By: Relevance
“…Our findings are consistent with past studies that have shown strong associations between the presence of a suicide plan and suicide attempts [3, 12]. While we are unaware of other studies investigating financial strain as a characteristic distinguishing suicide ideators and attempters, previous work has found that financial stressors may contribute to a substantial proportion of suicide attempts [23, 36].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with past studies that have shown strong associations between the presence of a suicide plan and suicide attempts [3, 12]. While we are unaware of other studies investigating financial strain as a characteristic distinguishing suicide ideators and attempters, previous work has found that financial stressors may contribute to a substantial proportion of suicide attempts [23, 36].…”
Section: Discussionsupporting
confidence: 92%
“…However, none have examined whether it is a risk factor for acting on suicide ideation. These studies may, therefore, be uninformative to clinicians, as many predictors of suicide ideation do not predict who will attempt suicide [2, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to violent movies and desensitization towards violence could be a component of this process. Correspondingly, a recent study [42] has identified violence, including fighting and weapon carrying, as an appropriate variable to differentiate between suicide ideators and attempters. The results of the present study warrant more research on the link between suicidality and the preference for horror movies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite key theoretical advances (e.g., Interpersonal-Psychological Theory of suicidal Behaviour: Joiner, 2005; The Integrated Motivational-Volitional Model of suicidal behaviour: O'Connor, 2011) our ability to predict, explain, prevent and differentiate between self-harm thoughts and behaviour is arguably unsatisfactory at present (Klonsky and May, 2014;Stack, 2014). Many people have feelings or experiences (e.g., thoughts, urges, mental imagery) that relate to self-harming.…”
Section: Self-harm Ideation Versus Self-harm Enactmentmentioning
confidence: 99%